ANALISIS KINERJA KEUANGAN SEBELUM DAN SAAT PANDEMI COVID-19 PADA SUBSEKTOR TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Karan, Ayu Agni Hastun; Challen, Auliffi Ermian (KRISNA: Kumpulan Riset Akuntansi, 2023)
Telecommunications is one of the sub-sectors that have benefited the most during the Covid-19 pandemic. Financial performance is one of the factors used to assess the good or bad of a company's development. Based on this, this study aims to find out how the company's financial condition in the telecommunications sub-sector was between before and during the Covid-19 pandemic and to analyze and find out the differences in the financial performance of the telecommunications sub-sector companies studied between before and during the Covid-19 pandemic. The financial performance studied is proxied by liquidity (current ratio), profitability (net profit margin), solvency (debt to assets), and growth (sales growth). This research uses descriptive quantitative type. The period before the Covid-19 pandemic was in 2018 quarters III and IV and in 2019 quarters I, II, III, and IV. While the research period after the Covid pandemic is in 2020 in the second, third and fourth quarters and in 2021 in the first, second, and third quarters. The population studied were 19 telecommunication sub-sector companies listed on the Indonesia Stock Exchange. Based on the purposive sampling method, the number of samples obtained was 4 companies. The results show that the current ratio, net profit margin, and debt to assets there are significant differences between before and during the Covid-19 pandemic in the telecommunications subsector, but the results of research on sales growth show that there is no significant difference between before and during the Covid-19 pandemic. 19 in the telecommunications subsector.